An Analysis Of Common Slang Words In Chris Brown Songs Lyric - Koupun, M.; Lumoindong, B.; Sanger, A. (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Like a bird without wings, human could not live without language. Human used language as a tool to communicate with one another, and as a forum for realizing their identity in social life. In everyday life, human used several types of language choices in communicating, such as official or standard language used in formal conversation situations, informal language used in everyday casual communication, and slang which is only used by certain groups of people when they send information to each other. This type of language was spoken by language users in casual situations or in their own community exclusively. This research focused on the forms of slang that appeared in the songs sung by Chris Brown. The aims of this research were to identify and analyze the types of slang words used in several Chris Brown songs lyric, and to explain their meaning. This research method was descriptive qualitative. After analyzing the slang words contained in Chris Brown's song lyrics, there were 19 data points successfully gained which covered 2 copy reduplications, 4 clippings, 12 coinages, and 1 blending. This research provided information that there were several forms of slangs that were only found in the lyrics of Chris Brown's songs and used only by certain groups of people. This research could be the entry point for further research related to slang words by other researchers who are interested in similar research.